Genome-wide analysis of the bZIP gene family and the role of AchnABF1 from postharvest kiwifruit (Actinidia chinensis cv. Hongyang) in osmotic and freezing stress adaptations. (July 2021) - Jin, Mijing; Gan, Sufu; Jiao, Jianqing; He, Yiheng; Liu, Hui; Yin, Xueren; Zhu, Qinggang; Rao, Jingping
Highlights: Identification and classification of bZIP members in kiwifruit. Transcriptome analysis of AcbZIP genes response to cold. Transcription profiles of AchnABF genes response to abscisic acid. Ectopic over-expression of AchnABF1 enhanced freezing and osmotic tolerance. Abstract: Chilling injury (CI) is a barrier to the refrigeration of kiwifruit, resulting in decreased fruit quality and increased nutrient loss during storage. Understanding the molecular basis underlying the cold response and its regulation in refrigerated kiwifruit is therefore highly important. Basic (region) leucine zipper (bZIP) transcription factors (TFs) have been widely studied for their roles in abiotic stress resistance in various species. In this study, we identified 81 bZIP family proteins in kiwifruit and classified them into 11 groups. Further transcriptome analysis revealed that the expression of members of the AREB/ABF family was strongly induced by low temperature and abscisic acid (ABA). Ectopic expression of AchnABF1 enhanced plant cold tolerance by upregulating the expression of several key genes associated with ABA-dependent and ABA-independent pathways in Arabidopsis thaliana . Reactive oxygen species (ROS) metabolism was suggested to be involved in the AchnABF1 -mediated osmotic stress response. For instance, enhanced ROS-scavenging ability was observed in transgenic plants with enhanced activity of catalase (CAT) and peroxidase (POD), which resulted in decreased in situ O2 .− and H2 O2 accumulation, ion leakage, and malondialdehyde (MDA) content under various abiotic stresses. In addition, AchnABF1 also participated in the osmotic stress response during both the germination and postgermination stages. We concluded that AchnABF1 may play an important role in kiwifruit during refrigeration.